A comparative study between I-gel and endotracheal tube for airway management in hypertensive patients undergoing elective laparoscopic cholecystectomy - Thapa, Puja; Rayamajhi, Mallika; Amatya, Biswa Ram; Shah, Aashish; Rijal, Thaneshwar; Gautam, Alok Raj; KC, Pradip (Journal of Patan Academy of Health Sciences, 2025)
Introduction: Laryngoscopy and endotracheal intubation during general anesthesia provoke sympathetic stimulation, resulting in transient but significant hemodynamic changes. These may be detrimental in hypertensive patients. The I-gel, a second-generation supraglottic airway device, may attenuate this response. This study compares the hemodynamic responses and perioperative outcomes of I-gel and endotracheal tube (ETT) in hypertensive patients undergoing elective laparoscopic cholecystectomy.Method: A hospital-based prospective, non-randomized, comparative observational study was conducted among ASA II hypertensive patients undergoing elective laparoscopic cholecystectomy. Airway management used I-gel or ETT per anesthesiologist preference, with the first 30 eligible patients assigned to each group. Hemodynamic parameters including heart rate (HR) and mean arterial pressure (MAP) were recorded at predefined intervals. Ease of insertion and perioperative complications were also compared.Result: A total of 60 patients were included in the study, with 30 in each group. The demographic parameters were comparable between the two groups. Time for insertion was significantly shorter in the I-gel group (11.34±0.78 s) than in the ETT group (13.42±1.31 s; p